1996
DOI: 10.1164/ajrccm.153.3.8630553
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a pneumonia practice guideline in an interventional trial.

Abstract: There are few available data to define the medically necessary duration of stay for patients hospitalized with pneumonia. Therefore, we investigated the safety and effectiveness of a practice guideline that provided information about switching patients from parenteral to oral antimicrobials and early hospital discharge. The study was a prospective controlled study with an alternate month design. The practice guideline was studied in 146 "low-risk" pneumonia patients hospitalized during a 22-month period. Medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0
3

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(62 citation statements)
references
References 23 publications
1
58
0
3
Order By: Relevance
“…They found improvements in the proportion of patients receiving antibiotics within 4 h, but not within 8 h. Overall length of stay significantly declined, although this was due to a drop in length of stay after conversion to oral antibiotics, without any change in the time to switch to oral antibiotics. Several other pneumonia intervention studies were not able to effect timely discharge or hospital length of stay [26][27][28]39 or time to first dose of antibiotics. 28 Our previous, single hospital study 29 demonstrated a significant decrease in the time from stability to switch to oral antibiotics and number of days of IV therapy and increase in patient education outcomes, but no reduction in length of stay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found improvements in the proportion of patients receiving antibiotics within 4 h, but not within 8 h. Overall length of stay significantly declined, although this was due to a drop in length of stay after conversion to oral antibiotics, without any change in the time to switch to oral antibiotics. Several other pneumonia intervention studies were not able to effect timely discharge or hospital length of stay [26][27][28]39 or time to first dose of antibiotics. 28 Our previous, single hospital study 29 demonstrated a significant decrease in the time from stability to switch to oral antibiotics and number of days of IV therapy and increase in patient education outcomes, but no reduction in length of stay.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 In order to overcome some of the limitations of these more passive attempts to improve pneumonia management, several more active approaches have been undertaken. Most of the published interventions in this field have primarily focused on one aspect of management, such as the admission decision, 22-25 length of stay, 26 -28 were aimed at lower risk patients, 26,27,29 or were limited to single institutions. 22,26,28 -30 Several of these studies 22,23 also had the added benefit of supplemental research nurses or other staff dedicated to implementing the intervention, circumstances that may not be easily replicable or sustainable in real-world practice where resources are much more limited While these studies have produced favorable improvements in some aspects of care, no multicenter study has sought to improve a broad spectrum of clinical quality, resource use, and patient education outcomes.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…For example, although pay-for-performance can improve quality, the type, amount, and timeliness of the incentives all affected the magnitude of the behavioral change and the potential benefit of the strategy. Second, most studies have selectively focused on only certain aspects of quality such as safety [22,31,75,76] and timeliness [12,52]. A complete evaluation of quality would require examination of all the elements.…”
Section: Discussionmentioning
confidence: 99%
“…Though seldom examined in isolation, non-physician healthcare providers, most commonly pharmacists and nurses, have facilitated guideline implementation and compliance in most randomized trials and before-andafter studies [223][224][225].…”
Section: Statement 39mentioning
confidence: 99%